Improving Student Attitudes in the Beginning Accounting Course. - Solomon, Lanny; De Coster, Don T. (The Accounting Review, 1975)
This article presents a study conducted to analyze the effect of differential instructional techniques upon the attitudes of students in an introductory accounting principles course. The introductory accounting principles course at many universities is frequently unsatisfactory to both faculty and students. Typically, it is a service course; i.e., it is a requirement for all business majors. Thus, the classes often contain a substantial number of students who have little or no interest in the subject matter. The principles course is one of the most important offerings of the accounting department for the simple reason that it usually determines those students who will become accounting majors. The students who: do poorly in material comprehension, or are not "turned on" by a highly mechanical and/or traditionally instructed course will find their areas of concentration in other disciplines. In the study, beginning accounting students at Case Western Reserve University were asked to respond to statements concerning Accounting Principles I, relating their answers to the course and its material content, not to the job their instructors did or did not do in their presentations.